(NgEOLOGI^ESKAQ \KSKURSIQ PO wOENNO(B-(NgRUZINSKOJ DOROGE (B:s (200 (NKILOMETROW GEOLOGI^ESKIH ZAGADOK(B) /s - (NmILXNI^UK(B, (NwIKTOR sTEPANOWI^s; (NnIKITINA(B, (NrIMMA gRIGORXEWNAs; (NqRO[ENKO(B, (NaLINA wIKTOROWNAs ((NmOSKWA (B:s (NnEDRA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 136s
(NbIBLIOGR(B.: (NS(B. 136s
Keywords: (NgEOLOGI^ESKIE \KSKURSIIs -- (NwOENNO(B-(NgRUZINSKAQ DOROGAs